Local preferences of mung bean qualities for food autonomy in India. Issue 2 (17th February 2017) - Singh, Shweta; Singh, Renu; Dahiya, Pradeep Kumar; van Boekel, M.A.J.S.; Ruivenkamp, Guido
ABSTRACT: The concept of food autonomy draws attention to qualities of local food and food networks that can facilitate connectivity between local food production and consumption. This article reports on a study conducted in Hisar, India, that reveals how rural producer, processor, and consumer preferences of mung bean quality interact with their aim to maintain and develop a territorial mung bean connectivity so as to reinforce food autonomy. The study showed that local mung bean food qualities related to suitability in the local cropping system, processing requirements, and consumption choice. It suggests that local preferences be integrated into a reorientation of research and scientific development agendas, and should become an essential consideration of development and extension efforts, which also carries implications for the food autonomy of local producers, processors, and consumers.